Urban gentrification and declining access to HIV/STI, sexual health, and outreach services amongst women sex workers between 2010-2014: Results of a community-based longitudinal cohort. (March 2020) - Goldenberg, Shira M.; Amram, Ofer; Braschel, Melissa; Moreheart, Sarah; Shannon, Kate
Abstract: Despite increasing gentrification across North American cities, little is known about impacts on work and living environments and health access for marginalized women. Drawing upon prospective cohort and external spatial data, we examined changes in land use and sex workers' work/living environments in relation to gentrification exposure in Metro Vancouver (2010–2014), and modeled independent effects of gentrification exposure on reduced utilization of HIV/STI testing, sexual health, and sex worker support services. These decreases occurred despite efforts to scale-up HIV services for marginalized populations. Planning of healthcare, housing, and other support services should be responsive to shifting urban landscapes for marginalized women. Highlights: Impact of gentrification on housing and service access for marginalized women is poorly understood. We used novel spatial-epidemiological methods to study gentrification-related changes. Gentrification exposure was linked to lower use of HIV/STI testing, sexual health, and support services. Policies that support access to safe housing, working environments, and services are needed. Scale-up of sex worker/community-led services in underserved areas is needed.